Study of the applicability of TiO2 as a decontaminating agent over treated metal surfaces - Fernández, Juan de Dios; del Campo, José María; Colorado, David (Revista de la Construcción. Journal of Construction, 2016)
The progressive deterioration we cause to the environment by exhalation of pollutants into our atmosphere is not sustainable. The degradation of air quality and pollution, caused by human activity, is endangering the very life of our species and the planet. For this reason, research and application of photocatalytic products with decontamination purposes has exponentially increased in recent years. In this article, the aim of this paper is to develop research and study of the use of vehicles is to develop not as pollutants, but as decontaminating substances through direct application to the bodywork of a product holding a Titanium Dioxide base, whose effectiveness has been demonstrated over asphalt pavements, and the study results. The results show values with a proven effectiveness, higher than products currently being marketed and used in different means. Once completed the analysis, several lines of research are initiated to improve the uses proposed.